A Planning Model for Village Fund Allocation in Infrastructure Development in Pattappa Village - S. Sarina; Muh. Ikbal; I Ketut Patra (Manunggal Halim Jaya, 2026)
This study aims to analyze the planning of Village Fund allocation for infrastructure development in Pattappa Village, Pujananting Subdistrict, Barru Regency. The study employed a qualitative approach using a case study method, with data collected through interviews, observation, and documentation. The findings show that Village Fund planning has been implemented in a participatory and sequential manner through hamlet deliberations and village development planning meetings. The process also refers to the Village Medium-Term Development Plan and the Village Government Work Plan in accordance with statutory provisions. However, planning effectiveness continues to face several constraints, including dynamic regulatory changes, limited capacity among village officials, and inadequate administrative support infrastructure at the village level. Strategic actors and community participation have functioned relatively well, although stronger coordination and capacity development are still needed to optimize sustainable village infrastructure development.